Tourism analytics: analysing visitor arrival data for tourism industry in Sarawak / Miko Chang May Lee and Clifford Kueh Wei Chyi - May Lee, Miko Chang; Kueh Wei Chyi, Clifford (2023)
Tourism is identified as one of the six key economic sectors in the Sarawak post-COVID-19 development strategy with an expected higher GDP contribution of 11% by 2030. Visitor arrival datasets have been commonly used to measure the performance of the tourism industry but their significance to the Sarawak tourism industry has not been clarified. This paper aims to fill in the research gap by examining the recent 20-year visitor arrival data in Sarawak and its relationship with the local tourism industry. Leveraging various data sources and advanced visualisation techniques, four research questions related to the market outlook, seasonality and plausibility of the visitor arrival statistics have been formulated and addressed.